Trigeminal neuralgia associated with ophthalmic surgery: a case series - María del Pilar Lucena; Federico Furno Sola; Mitzy E. Torres Soriano; Fanny Andrea Gerster (Journal of Medical Case Reports, 2018)
Abstract Background Trigeminal neuralgia is a rare cause of postoperative pain after ophthalmic surgery and has only been described twice in the international literature: one case of pain after vitrectomy with a crystalline lens extraction and another case of an unspecified surgery type. We report three cases of ophthalmic surgery-induced trigeminal neuralgia. Case presentation Trigeminal neuralgia was diagnosed in three patients after ophthalmic surgery. Patient 1 was a 63-year-old Caucasian man with an epiretinal membrane and cataract in his left eye. Phacovitrectomy was performed. Patient 2 was a 38-year-old Caucasian man with a perforating wound in his right eye. Primary closure of the cornea with removal of the necrotic iris was performed. Patient 3 was a 52-year-old Caucasian man referred 15 days after suffering blunt trauma to his right eye. Vitrectomy was performed to remove the crystalline lens, which was luxated to the vitreous. On postoperative days, these three patients were admitted to an emergency ward due to sudden, shock-like, one-sided facial pain activated by numerous stimuli. After consultation with specialists from the anesthesia and neurology departments, a diagnosis of trigeminal neuralgia was made. This diagnosis was based on the presence of four of the nine clinical criteria described by the International Headache Society, which were met in these three cases. Conclusions Trigeminal neuralgia is a rare cause of postoperative ophthalmic pain and is a challenging diagnosis for the ophthalmologist. It is necessary to consider the differential diagnosis of atypical pain after ophthalmic surgery.